News - Eva M. Riedmann (Taylor & Francis Group, 2012)
Two new combination pediatric vaccines advancing to use in infantsOncolytic viruses successfully delivered intravenouslyCuba eliminates hepatitis B among minors under 15Alzheimer's vaccine trial a successStudy: Shingles vaccine safe for patients on immune-suppressing drugsTherapeutic cancer vaccine against metastatic renal cell carcinoma enters Phase 3Pfizer's Men B vaccine shows promise in Phase 2Biovest initiates formal regulatory approval process for BiovaxID in Europe